2008
DOI: 10.1021/bp070334t
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Metabolic Activity of Filamentous Fungi Using a Colorimetric XTT Assay

Abstract: The filamentous nature and robust cell walls of many fungi render traditional measurements of active biomass (e.g., turbidity, dry cell weight) ineffective for most fungal bioprocesses. To overcome this challenge, an assay for quantification of overall metabolic activity is developed using 2,3-bis(2-methoxy-4-nitro-5-sulfophenly)-5-[(phenylamino) carbonyl]-2H-tetrazolium hydroxide (XTT), which in the presence of active mitochondria is converted to a water-soluble formazan derivative that absorbs light in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The tetrazolium salt XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide inner salt) (Sigma, St. Louis, MO) was used to measure the metabolic activity of A. fumigatus. Whereas XTT is a direct measure of the metabolic activity of cells, previous studies of A. fumigatus have indicated that XTT results are linear with mass and equated the XTT result with dry weight (19)(20)(21). Our confocal microscopy studies also address this point.…”
Section: Iron Chelators and Feclmentioning
confidence: 62%
“…The tetrazolium salt XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide inner salt) (Sigma, St. Louis, MO) was used to measure the metabolic activity of A. fumigatus. Whereas XTT is a direct measure of the metabolic activity of cells, previous studies of A. fumigatus have indicated that XTT results are linear with mass and equated the XTT result with dry weight (19)(20)(21). Our confocal microscopy studies also address this point.…”
Section: Iron Chelators and Feclmentioning
confidence: 62%
“…Cellular Metabolic Activity Assay-Colorimetric tetrazolium assay using the dye XTT {2,3-bis (2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino) carbonyl]-2H-tetrazolium hydroxide} was conducted to compare the WT and Sec cell metabolic activities as previously described (39). In brief, the WT spores and Sec mycelia were inoculated into SDB for 12 h and then transferred into 1 L flasks containing 300 ml SDB for 48 h at 28°C.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-fungal activity was assessed with the use of a calorimetric assay with 2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]2H-tetrazolium-5-carboxyanilide sodium salt (XTT; Sigma) and 2-methyl-1,4-napthoquinone (menadione; Sigma) as previously described [24]. Before each experiment, fresh stock solutions of XTT (5.75 mg/mL in PBS) and menadione (0.52 mg/mL in acetone) were prepared and stored at 4°C until required.Working XTT-menadione solution was prepared by combining XTT and menadione stock solutions at a ratio of 4:1.…”
Section: Fungal Hyphal Damage Assaymentioning
confidence: 99%
“…The anti-hyphal activity of the expanded panfungal T cells was assessed through the use of a colorimetric XTT reduction assay [24]. The percentages of hyphal damage toward A flavus, C albicans, C krusei, R oryzae and S prolificans were 81.7 ± 0.6 (n = 2), 25.1 ± 9.9 (n = 5), 9.8 ± 5.7 (n = 5), 8.7 ± 6.3 (n = 2), Table IV.…”
Section: Anti-hyphal Activity Of Cultured Panfungal T Cellsmentioning
confidence: 99%